A Systematic Review of Transition Readiness in Youth with Chronic Disease. (July 2020) - Varty, Maureen; Popejoy, Lori L.
The transition of chronically ill adolescents and young adults to adult health care is poorly managed, leading to poor outcomes due to insufficient disease knowledge and a lack of requisite skills to self-manage their chronic disease. This review analyzed 33 articles published between 2009 and 2019 to identify factors associated with transition readiness in adolescents and young adults with chronic diseases, which can be used to design effective interventions. Studies were predominantly cross-sectional survey designs that were guided by interdisciplinary research teams, assessed adolescents and young adults ages 12–26 years, and conducted in the outpatient setting. Modifiable factors, including psychosocial and self-management/transition education factors, and non-modifiable factors, including demographic/ecological and disease factors, associated with transition readiness were identified. Further research is necessary to address gaps identified in this review prior to intervention development, and there is a need for additional longitudinal studies designed to provide perspective on how transition readiness changes over time.